The Use of Digital Tools Scaffolding Language Teaching During Pandemic Outbreak of Covid 19 at State Schools in Turkey - Ümit Özkanal (Anadolu Üniversitesi Eğitim Fakültesi dergisi, 2022)
The study aims to investigate what digital tools were used to scaffold language teaching during the pandemic outbreak of Covid-19. In addition to the list of the digital tools used at K12 classrooms, the reasons to use these tools were examined to discuss their functions to scaffold language teaching dynamics. This study was designed as a descriptive study adopting a qualitative research method. To obtain objective observation data, 43 pre-service teachers attending teaching practice at different K12 schools participated in the study and their reflective observations regarding which digital tools they used, how and why they used them were analyzed. The qualitative analysis indicated that the teachers used different digital tools during online lessons and they varied the tools to increase student involvement and to offer extra interactive activities to revise the target structure. Utilizing these tools and implementations, their lessons were reported as more effective, fun and interactive.